Piezoelectric Dynamics of Arterial Pulse for Wearable Continuous Blood Pressure Monitoring - Yi, Zhiran; Liu, Zhaoxu; Li, Wenbo; Ruan, Tao; Chen, Xiang; Liu, Jingquan; Yang, Bin; Zhang, Wenming (Advanced materials (Weinheim), 2022)
Piezoelectric arterial pulse wave dynamics are traditionally considered to be similar to those of typical blood pressure waves. However, achieving accurate continuous blood pressure wave monitoring based on arterial pulse waves remains challenging, because the correlation between piezoelectric pulse waves and their related blood pressure waves is unclear. To address this, the correlation between piezoelectric pulse waves and blood pressure waves is first elucidated via theoretical, simulation, and experimental analysis of these dynamics. Based on this correlation, the authors develop a wireless wearable continuous blood pressure monitoring system, with better portability than conventional systems that are based on the pulse wave velocity between multiple sensors. They explore the feasibility of achieving wearable continuous blood pressure monitoring without motion artifacts, using a single piezoelectric sensor. These findings eliminate the controversy over the arterial pulse wave piezoelectric response, and can potentially be used to develop a portable wearable continuous blood pressure monitoring device for the early prevention and daily control of hypertension. Piezoelectric dynamics of arterial pulse first elucidate the correlation between piezoelectric pulse waves and blood pressure waves. It is feasible to achieve wearable continuous blood pressure monitoring without motion artifacts, using a single piezoelectric sensor. This strategy may provide new insights on the development for wearable continuous blood pressure monitoring.